INTEGRASI KADER NAHDLATUL ULAMA (NU) KE DALAM PARTAI PDI-PERJUANGAN DI PROVINSI RIAU - ,, Ahmad; ,, Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The phenomenon of political integration between Nahdlatul Ulama (NU) cadres and Partai Demokrasi Indonesia Perjuangan (PDI-P) in Riau Province demonstrates an interesting shift in political orientation. NU, as a religious organization with a large mass base and moderate Islamic views, and PDI-P as a nationalist party that upholds the Pancasila ideology, created a new political dynamic when NU cadres chose to become active in PDI-P. This phenomenon raises questions about the factors driving this integration and how the process unfolded in the local context. This study aims to understand the reasons and motivations of NU cadres to join the PDI-P and to analyze the extent to which shared values, strategic interests, and historical backgrounds influence their political choices. This study uses qualitative methods and a case study approach, where data were collected through in-depth interviews with seven informants who are NU cadres and active in the PDI-P, as well as documentation and participant observation to enrich the data. Research results indicate that this integration was driven by shared values, nationalism, and moderation, the inclusive vision of the PDI-P leadership, and individual motivations such as organizational experience, personal beliefs, and political aspirations. This integration process was strategic and reciprocal, providing NU cadres with a channel for struggle in the formal political sphere while simultaneously strengthening PDI-P's religious base. Keywords: Political Integrationm Nahdlatul Ulama, PDI-Perjuangan, Political Motivation